Work as a recovery factor after earthquake: a mixed-method study on female workers. Issue 4 (31st July 2019) - Galanti, Teresa; Cortini, Michela
Abstract : Purpose: The purpose of this paper is to investigate the reaction of female workers to the earthquake event that shocked the city of L'Aquila in April 2009, with a specific focus on work as a recovery factor. Design/methodology/approach: The selected sample consists of current or former resident women in the affected province of L'Aquila, who participated in a series of focus group discussions on the ability to reconstruct their own professional identity after the earthquake. The focus group seemed to be the perfect instrument for this research, because of its ability to generate a true discussion among a group of people on the research topic of this study. The collected data were analyzed both in terms of metaphors, as well as linguistic agentivity and by automatic content analysis. Findings: From the analysis of the data, emerges the value that adds to the sense of identity continuity for the women in the sample, together with interesting differences between employed and self-employed workers that are characterized by distinct challenges and assurances. In regards to the effects of gender in response to disaster events, the results make a peculiar echo to the studies on public-private space dichotomy developed by Fordham, according to which, during a disaster, women are not allowed to develop work-related desires. For the group of women that the authors interviewed, the challenge to have family focused or work focused desires was clearly evident; they seem predetermined to the above-mentioned dichotomy, valid in both directions: the women who invested in work and have become entrepreneurs seem to have no chance of a private life and, on the contrary, the women who were focused on more traditional family roles seem to have no chance in terms of job opportunities. Originality/value: Based on the authors' knowledge this is the first time that focus groups are used to assess the value that work had in supporting individual recovery for women in the aftermath of the L'Aquila earthquake.